AMELIORATIVE EFFECT OF BERBERIS VULGARIS FRUIT EXTRACT AGAINST GENTAMICIN INDUCED NEPHROTOXICITY IN ALBINO RATS - Faisal, Lubna; Islam, Zia -Ul-; Athar, Saima; Iqbal, Sadia; Rehman, ```Fatima; Ullah, Syed Shariq (Pakistan Armed Forces Medical Journal, 2021)
Objective: To observe the nephroprotective role of berberis vulgar is on renal parenchyma against microscopic and morphometric changes induced by Gentamicin in albino rats. Study Design: Lab based experimental study. Place and Duration of Study: It was conducted in Baqai Medical University in collaboration with department of Anatomy Liaquat National Hospital and Medical College, from Jan to Jul 2017. Methodology: A total of 40 male adult albino rats were used in the study. Four groups were made. Each group contained 10 rats. Group A was a control group, group B received only berberis vulgaris fruit extract orally per day for 21 days, group C received Gentamicin 100 mg/kg/day intraperitonially daily for 21 days. Group D received Gentamicin 100 mg/kg/day intraperitonially along with berberis vulgaris fruit extract 100 mg/kg/day orally. Both kidneys were removed. H&E and PAS stains were used for observing histological alterations and protective role of berberis vulgaris fruit extract. Results: Glomerulus and proximal convoluted tubules were observed histologically in all 4 groups. Microscopy of group B showed parameters nearly similar to control group. Microscopy of group C showed significant derangement in all parameters when compared with control group. Group C showed decrease glomerular, proximal convoluted tubular count was noted. Glomerular diameter increases and there was glomerular hypertrophy and tubular necrosis. Microscopy of group D showed significant improvement due to berberis vulgaris which restored normal renal architecture. Conclusion: Berberis vulgaris has a nephroprotective effect and it can be used as a new medicine against nephrotoxic drugs like Gentamicin.